The Effect of Early Mobilization on Pulmonary Function Recovery in Post-Abdominal Surgery Patients - Wahyuni, Tri; Ibrahim, Sultan Akbar (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Background: Post-abdominal surgery patients often experience impaired lung function due to pain, decreased lung expansion, and prolonged immobilization. Early mobilization is one of the recommended non-pharmacological interventions to accelerate lung function recovery. Objective: This study aims to analyze the effect of early mobilization on the recovery of lung function in post-abdominal surgery patients. Method: This study uses a quasi-experimental design with a pretest-posttest approach. control group. A sample of 40 patients was divided into an intervention group (n=20) who were given early mobilization 6–12 hours after surgery, and a control group (n=20) who were given mobilization according to standard hospital procedures. Pulmonary function parameters were measured using spirometry (Forced Vital Capacity / FVC and Forced Expiratory Volume in 1 second/FEV1) on days 1 and 3 postoperatively. Data analysis used paired t-test and independent t-test with a significance level of p<0.05. Results: The study showed a significant increase in FVC and FEV1 values in the intervention group compared to the control group (p=0.001). Patients who underwent early mobilization had faster lung function recovery, with a reduced incidence of respiratory complications such as atelectasis. Conclusion: Early mobilization is effective in accelerating the recovery of lung function in patients following abdominal surgery. Implementation of early mobilization can be used as a standard intervention in postoperative care to prevent respiratory complications.